Kehadiran Linguistik, Falogosentris dan Pendidikan Kristen Dalam Percakapan Filosofi Luce Irigaray - Munte, Alfonso (Badan Litbang dan Diklat Kementerian Agama RI, 2023)
Linguistic issues that are intertwined and/or related to gender are often researched from sociolinguistic circles, including friends from feminism. Researchers see that there is a special space for Luce Irigaray's philosophical lens which is more balacing, namely women are able to create their own language without the need for subordinate appraisal. Previously, throughout the history of male-dominated philosophers, there was a massive amount of an alienated philosophical perspective when encountering (meta)linguistics. The purpose of this study is to investigate philosopher Luke Irigaray's views on his disagreement with the distinction between men and women in the world of linguistics, including linguistics in daily worship in Christianity. This qualitative research design uses literature study as the basis to collect data on the emergence of linguistics through journals and books on linguistics, morphology and/or Christianity. Then, the data is analyzed through Luke Irigaray's views when talking about equal respect between the sexes and rejecting subordination/alienation. The results show that sexual difference goes beyond biological terms. Moreover, it lies in the historical civilization of language. Non-segregated language then accepts ambiguity, paradox, and ambivalence. For her, women have a natural sociability that leads to intersubjective communication in addition to being a symbolic weapon of the superior state.